Extending the innovation characteristic model to private label products: brand trust as the new innovation characteristic - Wee, Stany Lian Fong; Hishamuddin Ismail; Tan, Pei Kian (Penerbit Universiti Kebangsaan Malaysia, 2023)
In innovation adoption, potential adopters are expected to rely on the brand name of the innovation to determine its quality level. Because risks are involved in most innovation adoption, dependency appears between the consumer and the brand. With little attention being put to analyze brand trust in consumer brands and diffusion studies, this study conceptually proposes an innovation characteristic model which includes brand trust as the new innovation characteristic and mediates existing characteristics to adoption intention in the existing literature. Certain private label products are also selected as the innovation subject herein and are expected to draw retail practitioners' attention to the importance of brand management. Retailers' efforts are deemed worthless if retailers do not pay attention to brand trust, which is the underlying cause of private label failure in developing markets. The empirical results herein are expected to aid in augmenting the influence of brand trust on any innovation adoption and further highlight the importance of brand management for retail and private label brands.